ATRT-07. TARGETING PRIMARY CILIOGENESIS IN ATYPICAL TERATOID/RHABDOID TUMORS. (23rd April 2019) - Blümel, Lena; Kerl, Kornelius; Qin, Nan; Berlandi, Johannes; Thiel, Katharina; Tegeder, Isabel; Jeibmann, Astrid; Paisana, Eunice; Custódia, Carlos; Picard, Daniel; Langini, Maike; Stühler, Kai; et al.
Abstract: Atypical teratoid/rhabdoid tumors (AT/RT) are among the most common malignant brain tumors in infants. Comprehensive genomic studies revealed three distinct molecular subgroups (AT/RT-TYR, -MYC and -SHH). As primary cilia (PC) have already been shown to play a pivotal role in other tumor entities, we aimed to characterize the distribution of PC across AT/RT subgroups and to target primary ciliogenesis in these tumors with dismal prognosis. We performed immunofluorescence to detect PC in AT/RT primary tumor sections and cell lines. The functional role of PC was investigated in vitro by knockdown of KIF3A . The relevance of primary ciliogenesis in AT/RT biology was further elucidated in vivo using a fly model of SMARCB1 deficiency and an orthotopic mouse model. We detected PC in all AT/RT primary tumor sections and cell lines investigated in this study. Notably, we observed a significant subgroup-specific difference in the proportion of PC-positive cells. Specifically, AT/RT-TYR demonstrated the highest percentage of ciliated cells. Knockdown of KIF3A significantly reduced cell proliferation and stem cell properties. Additionally, apoptosis was significantly increased via upregulation of JAK1/STAT1 signaling. In a fly model of SMARCB1 deficiency, concomitant knockdown of several cilia-associated genes resulted in a substantial shift of the lethal phenotype with >20% of flies reaching adulthood. Finally, we demonstrated a significantly prolonged survival in an orthotopic xenograft model upon knockdown of KIF3A . In conclusion, our results implicate PC as a key feature of AT/RT biology and suggest primary ciliogenesis as a potential therapeutic target, especially in AT/RT-TYR.